HUBUNGAN KECEMASAN BERBICARA DENGAN HASIL BELAJAR BAHASA INGGRIS SISWA KELAS III SD MUHAMMADIYAH 05 MEDAN - Utari; Rinaldy Alidin; Yuni Wulandari (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study aims to examine the relationship between speaking anxiety and English learning outcomes among third-grade students at SD Muhammadiyah 05 Medan. Speaking anxiety is assumed to be one of the affective factors that may hinder students’ language performance, even when they have cognitively understood the learning material. This study employs a quantitative approach using a correlational research design. Data are collected through a speaking anxiety questionnaire and documentation of students’ English learning scores, and are subsequently analyzed using the Pearson Product-Moment correlation test. The findings of this study are expected to provide empirical evidence regarding the contribution of psychological factors to English learning achievement among elementary school students. In addition, the results may serve as a reference for teachers in designing English learning activities that are more affectively supportive and responsive to students’ emotional needs.